DIAGNOSIS DAN STRATEGI PENANGANAN NYERI LEHER FOKUS PADA MIELOPATI SPONDILOSIS - Endang Mutiawati Rahayuningsih* (Neurona Majalah Kedokteran Neuro Sains, 2015)
PAIN IS A TERM USED TO EXPRESS THE PRESENCE OF PAIN IN THE BACK OF THE NECK AREA BOTH LOCALLY AND RADIATING TO THE OCCIPITAL SHOULDERS AND ARMS THE MAIN CAUSES OF NECK PAIN INCLUDE DEGENERATIVE PROCESSOF THE CERVICAL SPINE VERTEBRAL BODIES JOINTS LIGAMENTS INTERVERTEBRAL DISCS RADICULOPATHY AND MYELOPATHY RARELY NECK PAIN CAN BE CAUSED BY TRAUMA NEOPLASM AND OTHER DISORDERS